Perancangan dan Implementasi Aplikasi Sistem Pakar Untuk Diagnosa Gangguan Kehamilan Menggunakan Metode Bayes - Leva Affrillianggi Falihah; Slamet Santoso; Silvia Elrahman (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2017)
During pregnancy, pregnant women generally experience various kinds of pregnancy disorders, both mild and severe. To diagnose this problem, ideally it requires consultation with an expert, in this case a midwife or obstetrician (obstetrician and gynecologist) so that the provision of solutions is more accurate and effective. With the rapid advancement of computer technology as it is now helping people in various fields of life, one of which is the health sector. One of the computer technologies used is Artificial Intelligence. Artificial intelligence can make computers easier to use with displays that use natural language so that they are easy to understand, and one part of an artificial intelligence system is an expert system. Expert Systems are computer-based systems that use knowledge, facts and reasoning techniques to solve problems that normally only an expert in the field can solve. Thus, an expert system can also be used to assist in diagnosing disorders of pregnancy.